2005
DOI: 10.1139/t04-084
|View full text |Cite
|
Sign up to set email alerts
|

Influence of groundwater on the bearing capacity of shallow foundations

Abstract: In this paper, the kinematic approach of limit analysis is used to analyse the influence of groundwater on the bearing capacity of shallow foundations. Analytical expressions are derived allowing the bearing capacity of strip footings resting on a soil where the water table is at some depth below the footing base to be calculated. Results from these expressions are compared with those obtained using other theoretical solutions available in literature. Moreover, a parametric study is carried out to illustrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Fluctuations in GWL have a negative impact on the foundations of various buildings and infrastructures due to ground subsidence and reductions in bearing capacity [5,6]. It is challenging to predict and estimate GWL and its variations, which are strongly related to meteorological characteristics [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluctuations in GWL have a negative impact on the foundations of various buildings and infrastructures due to ground subsidence and reductions in bearing capacity [5,6]. It is challenging to predict and estimate GWL and its variations, which are strongly related to meteorological characteristics [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no apparent indications of failure or collapse conditions, changes in GWL can cause a considerable amount of ground subsidence and instant instability problems, all of which are related to the functionality and performance of target structures [2,3]. Various investigations into the effects of GWL on the performance of foundation structures have been performed, and design methods to take GWL into account have been proposed [4][5][6][7]. The results from these investigations indicated that incorporation of GWL into the design is essential to guarantee the sustainable performance of structures and to prevent unexpected damage during the lifetime of the structures due to additional settlement or reductions in bearing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…As the water does not flow within the rock mass, the work due to seepage forces will be equal to zero. Ausilio and Conte (2005) used this approach to obtain the bearing capacity of foundations on submerged soils. The total energy dissipation is similar to the dry case.…”
Section: Bearing Capacity Of Foundations On Submerged Rocksmentioning
confidence: 99%
“…Since there is no published document for determining the effect of groundwater on the bearing capacity of rock masses, the results obtained using the upper bound solution were compared to the methods of Hansen et al (1987) and Ausilio and Conte (2005) for determining the bearing capacity of foundations on submerged soils. For greater compatibility in the results, the same c and / for the intact rock and the joint sets were used and the symmetrical mechanism (TS1) was selected for comparison.…”
Section: Comparison With the Existing Solutionsmentioning
confidence: 99%
“…Increasing freezing-thawing cycles within the soil zone cause changes in various soil properties such as permeability, volume change behavior, strength, and compressibility [7][8][9]. Unusual fluctuation of groundwater level due to changes in annual precipitation characteristics causes additional settlements and unexpected reduction in the bearing capability of foundations [10][11][12]. All these threaten the stability and sustainability of the electrical transmission tower system, highlighting the need for a more robust and resilient structural system with certain reinforcements.…”
Section: Introductionmentioning
confidence: 99%